MiR‐135b is a direct PAX6 target and specifies human neuroectoderm by inhibiting TGF‐β/BMP signaling. (6th May 2014) - Bhinge, Akshay; Poschmann, Jeremie; Namboori, Seema C; Tian, Xianfeng; Jia Hui Loh, Sharon; Traczyk, Anna; Prabhakar, Shyam; Stanton, Lawrence W
Abstract Several transcription factors (TFs) have been implicated in neuroectoderm (NE) development, and recently, the TF PAX6 was shown to be critical for human NE specification. However, microRNA networks regulating human NE development have been poorly documented. We hypothesized that microRNAs activated by PAX6 should promote NE development. Using a genomics approach, we identified PAX6 binding sites and active enhancers genome‐wide in an in vitro model of human NE development that was based on neural differentiation of human embryonic stem cells (hESC). PAX6 binding to active enhancers was found in the proximity of several microRNAs, including hsa‐miR‐135b. MiR‐135b was activated during NE development, and ectopic expression of miR‐135b in hESC promoted differentiation toward NE. MiR‐135b promotes neural conversion by targeting components of the TGF‐β and BMP signaling pathways, thereby inhibiting differentiation into alternate developmental lineages. Our results demonstrate a novel TF‐miRNA module that is activated during human neuroectoderm development and promotes the irreversible fate specification of human pluripotent cells toward the neural lineage.